MODIFIKASI STRUKTUR ZAT WARNA KUINOLIN UNTUK MENINGKATKAN KINERJA SEL SURYA MENGGUNAKAN METODE DFT - Elvira Deswita; Imelda Imelda; Rifky Farhan; Oesamah Oesamah (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2021)
In this study, Quinoline-based D-H-A organic dye was used which consisted of 4 dyes with various donor chains of aniline (Q1), indoline (Q2), phenol (Q3) and coumarin (Q4). The calculation method used is the DFT/TD-DFT (Density Functional Theory/Time Dependent-DFT) method with a B3LYP / 6-31G basis set. The aim of this study was to determine the modification of the quinoline-based D-H-A dye with variations of the donor chains are efficient as a sensitizer on DSSC. Analysis based on the parameters of the bandgap, wavelength absorption, excitation energy, G-inject, G-reg, oscillator strength, dihedral angle, bond length, dipole moment, LHE and Voc. The result of the study show O2 with the name 6-(indolin-5-yl) quinoline-2-carboxylic acid is the best dye with a bandgap is 2,6204 eV, absorption wavelength is 566,80 nm, excitation energy is 2,1875 eV, G-inject is -3,114 eV, G-reg 0,1239 eV. Therefore, it can be concluded that the modification of quinoline dye to D-H-A type can improve the performance of DSSC.